Air assisted impact of drops: The effect of surface wettability. (May 2020) - Singh, Ramesh Kumar; Mandal, Deepak Kumar
Highlights: Airflow assisted impact of drops on surfaces with various wettabilities is studied. The spreading reduces at higher airflow and Weber number for less wetting surfaces. Combined action of airflow shear and normal imposed pressure is responsible. The comparison of measured spread with a model improves when wettability reduces. Abstract: The airflow assisted impact of water drops on surfaces with various wettabilities is studied to understand the effect of shear force and normal imposed pressure provided by the incident airflow. Results show that the maximum spreading factor increases with the impact Weber number for the drops impacting a hydrophilic surface. For other surfaces, the spreading increases with the airflow for a given Weber number. However, the factor is observed to suddenly decrease at higher Weber numbers and airflow and for the less wetting surfaces. For the hydrophilic surface, as the drop continues spread, higher adhesive force between the drop and surface causes the rim to become thinner. The shear force pushes the rim outward. As the wettability decreases, a deceleration is observed at the early stage of spreading, forming fingers and thicker rim at the last stage. The thicker rim causes the viscous dissipation to decrease suddenly for the highest Weber number and airflow tested. The thicker rim resists the drop to spread. Detachment of the satellite drops on a hydrophilic surface increases with the airflow since the shear force increases. The normal imposed pressure applies pressure on the fingers and gives momentum to the lamella in the radial direction. A comparison of the measured maximum spreading with the one obtained from an existing model, is provided. Better comparison is found for the cases of less wetting surfaces, whereas good comparison is observed only at higher impact Weber numbers for the hydrophilic surface. Graphical abstract: Image, graphical abstract